Тransplastomic tobacco plants producing the hydrophilic domain of the sheep pox virus coat protein L1R - D. K. Beisenov; G. E. Stanbekova; B. K. Iskakov (Вавиловский журнал генетики и селекции)
Sheep pox has a wide geographical range of distribution and poses a threat to sheep breeding worldwide, as the disease is highly contagious and is accompanied by large economic losses. Vaccines based on live attenuated virus strains are currently being used for prevention of this disease. Such vaccines are effective, but potentially dangerous because of the possible virus reversion to a pathogenic state. The development of safe recombinant subunit vaccines against sheep pox is very relevant. The high ploidy level of the plant chloroplasts makes it possible to obtain large quantities of foreign proteins. The purpose of this study was to create transplastomic Nicotiana tabacum plants producing one of the candidate vaccine proteins of sheep pox virus L1R. A vector containing a deletion variant of the SPPV_56 gene, which encodes the N-terminal hydrophilic part of the viral coat protein L1R, was constructed to transform tobacco plastids. It provides integration of the transgene into the trnG/trnfM region of the chloroplast tobacco genome by homologous recombination. Spectinomycin-resistant tobacco lines were obtained by biolistic gun-mediated genetic transformation. PCR analysis in the presence of gene-specific primers confirmed integration of the transgene into the plant genome. Subsequent Northern and Western blot analysis showed the gene expression at the transcriptional and translational levels. The recombinant protein yields reached up to 0.9 % of total soluble protein. The transplastomic plants displayed a growth retardation and pale green leaf color compared to the wild type, but they developed normally and produced seeds. Southern blot analysis showed heteroplasmy of the plastids in the obtained plants due to recombination events between native and introduced regulatory plastid DNA elements. The recombinant protein from plant tissue was purified using metal affinity chromatography. Future research will be focused on determining the potential of the chloroplast-produced protein to induce neutralizing antibodies against SPPV strains.